2020
DOI: 10.1177/1947603520967077
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification of Intact Porcine Femoral Condyle Allografts Using an Optimized Approach

Abstract: Objective Successful preservation of articular cartilage will increase the availability of osteochondral allografts to treat articular cartilage defects. We compared the effects of 2 methods for storing cartilage tissues using 10-mm diameter osteochondral dowels or femoral condyles at −196°C: (a) storage with a surrounding vitrification solution versus (b) storage without a surrounding vitrification solution. We investigated the effects of 2 additives (chondroitin sulfate and ascorbic acid) for vitrification o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…Our data revealed the inability of the traditional convection method for large OCA preservation and showed that improving the heating rate is needed to achieve large cartilage cryopreservation. Our findings are aligned with a recent literature report 47 . In this prior literature study, CPA solutions surrounding the condyle were depleted, enabling faster heat transfer due to direct contact between the cartilage and water bath 47 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data revealed the inability of the traditional convection method for large OCA preservation and showed that improving the heating rate is needed to achieve large cartilage cryopreservation. Our findings are aligned with a recent literature report 47 . In this prior literature study, CPA solutions surrounding the condyle were depleted, enabling faster heat transfer due to direct contact between the cartilage and water bath 47 .…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are aligned with a recent literature report 47 . In this prior literature study, CPA solutions surrounding the condyle were depleted, enabling faster heat transfer due to direct contact between the cartilage and water bath 47 . In contrast, in our nanowarming method, the surrounding CPAs remained and were rapidly warmed through nanowarming to achieve fast heat transfer and an elevated heating rate.…”
Section: Discussionsupporting
confidence: 93%
“…The ImageJ software was then used to count the cells in the images, and chondrocyte viability was calculated as the percentage of live cells relative to the total number of cells. In each cartilage slice, the chondrocyte viability was determined as the percentage of green cells relative to the total number of green and red cells 28,35 . The experimental procedures were repeated two times.…”
Section: Methodsmentioning
confidence: 99%
“… 7 , 9 , 19 , 25 Multiple attempts have been made to cryopreserve AC; however, it was not until recently that successful cryopreservation protocols were developed. 7 , 9 , 18 , 19 , 37 , 39 Optimized protocols for the long-term storage of osteochondral dowels 18 and more recently particulated AC cubes (~1-mm 3 cubes) have been developed. 37 Based on extensive previous research on the vitrification of AC, # mathematical modeling has been used to identify and screen potential loading parameters that included cryoprotectant concentration, exposure time, toxicity, and temperature.…”
mentioning
confidence: 99%
“… 7 , 9 , 18 , 19 , 37 , 39 Optimized protocols for the long-term storage of osteochondral dowels 18 and more recently particulated AC cubes (~1-mm 3 cubes) have been developed. 37 Based on extensive previous research on the vitrification of AC, # mathematical modeling has been used to identify and screen potential loading parameters that included cryoprotectant concentration, exposure time, toxicity, and temperature. 39 Protocols were tested on swine and human particulated cartilage to ensure that chondrocyte viability was maintained (>80% viable) after vitrification and rewarming.…”
mentioning
confidence: 99%